Finite element analysis of different spinal cage designs for posterior lumbar interbody fusion - Mahendran, Kugendran; Muhammad Hilmi, Jalil (Kyushu University, 2021)
The study on spinal cage designs for their implementation in the medical field is developing over the years. Currently, many designs have been studied varying from the biomaterials and the designs. This study aimed to determine the best design structure of an annealed titanium spinal cage with the integration of porous holes and to attain its mechanical performance under different loadings before topology optimization. 8 specimens were designed and analyzed based on porosity percentage, MIT, and FEA before undergoing topology optimization. The analysis was conducted on two loadings applied simultaneously to resemble the human body weight and the motion of the lumbar column. Results showed that the stress concentration of all specimens increased accordingly as the porosity volume increases, thus specimen 2 was selected due to it having the second-lowest stress concentration but also the more adequate pore volume for the bone graft filling.